Interaction of nanoparticles with biological systems - Vass, István Zoltán; Deák, Zsuzanna; Paul, Kenny; Kovács, Sándor; Vass, Imre (Acta Biologica Szegediensis, 2015)
Nanoparticles (NPs) are literally and figuratively infiltrating all fields of biological research. They are sophisticated tools that can be customized, either by smart engineering or by the attachment of specific ligands, to match the requirements of a particular task. Through their inherent and functionalized properties they are the basis for new developments while enhancing the efficiency of already existing techniques or rendering methods to be more specific. They provide new approaches for therapeutic applications and brand new platforms for diagnostic processes. In this review we provide an insight into the practical applications of NPs, emphasizing their use in biosensing, bioimaging, biomolecule delivery systems and enzyme immobilization. Since the interest in the interactions of NPs and biological systems is fairly new, we also elaborate on the drawbacks of their practical applications by reporting their potential toxicity in in vitro and in vivo systems.